Service Quality Analysis with Pivotal-Core-Peripheral (PCP) Model (Case Study: Restu Ibu Hospital Balikpapan) - Cahya, Hadifah Mutiara; Pawitra, Theresia Amelia; Widada, Dharma (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Restu Ibu Hospital in Balikpapan is a private healthcare provider offering various clinics, including a neurology clinic. This study aims to measure the quality of service at Restu Ibu Hospital from the perspective of BPJS patients at the neurology clinic using the Pivotal Core Peripheral (PCP) model. Additionally, the study provides suggestions for improving service quality where it falls short of patient expectations. The PCP model assesses service quality through three main attributes: Pivotal, Core, and Peripheral. The research findings indicate that the Pivotal attribute has the lowest score of 0.103, meaning that the service meets patient expectations. The Core attribute has a score of 0.349, also indicating that the service meets patient expectations. Meanwhile, the Peripheral attribute has the highest score of 0.503, suggesting that this aspect of service exceeds patient expectations. Overall, the average score for PCP attributes is 0.318, indicating that all attributes are within the range of patient expectations. Patient satisfaction scores for the neurology clinic and the hospital overall are 3.61 and 3.52, respectively, reflecting a general satisfaction with the services at Restu Ibu Hospital. However, there are still two areas under the Pivotal attribute that fall below patient expectations: waiting time at the pharmacy, with a score of -0.68, and waiting time at registration, with a score of -0.59. Suggested improvements include enhancing the queue management system by providing information on the remaining queue, educating patients on using the application for easier registration, increasing human resources, and improving facilities for patient comfort.